2023
DOI: 10.3389/fgene.2023.1049608
|View full text |Cite
|
Sign up to set email alerts
|

Salinity stress endurance of the plants with the aid of bacterial genes

Abstract: The application of plant growth-promoting bacteria (PGPB) is vital for sustainable agriculture with continuous world population growth and an increase in soil salinity. Salinity is one of the severe abiotic stresses which lessens the productivity of agricultural lands. Plant growth-promoting bacteria are key players in solving this problem and can mitigate salinity stress. The highest of reported halotolerant Plant growth-promoting bacteria belonged to Firmicutes (approximately 50%), Proteobacteria (40%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…In studies in which these bacteria have been identified, the habitat is not characterized by strong salinity, as in salt marshes. The dominant position of these bacteria in conditions of radioactive contamination can be explained by their high resistance to oxidative stress, accompanying halotolerance [336,337]. In some cases, it can be assumed that bacteria have entered the soil of radioactively contaminated areas from external sources, such as the deep-sea representative Marinilactibacillus piezotolerans [27], which could have been introduced as a result of a tsunami following an earthquake and causing the accident at the Fukushima Daiichi Nuclear Power Plant.…”
Section: Halotolerancementioning
confidence: 99%
“…In studies in which these bacteria have been identified, the habitat is not characterized by strong salinity, as in salt marshes. The dominant position of these bacteria in conditions of radioactive contamination can be explained by their high resistance to oxidative stress, accompanying halotolerance [336,337]. In some cases, it can be assumed that bacteria have entered the soil of radioactively contaminated areas from external sources, such as the deep-sea representative Marinilactibacillus piezotolerans [27], which could have been introduced as a result of a tsunami following an earthquake and causing the accident at the Fukushima Daiichi Nuclear Power Plant.…”
Section: Halotolerancementioning
confidence: 99%
“…Accordingly, sequencing, mass spectrometry, and other metabolomics techniques can greatly facilitate the identification of high-throughput molecules for the efficient use of PGPB [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation management practices, such as the use of drip irrigation or the recycling of drainage water, can also help to reduce the amount of salt entering the soil. Overall, managing the impacts of high sodium levels in water on soil health is crucial for ensuring sustainable agriculture and protecting ecosystem health (Zamanzadeh-Nasrabadi et al, 2023;Mohanavelu et al, 2021;Agudelo et al, 2016;Musie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%